Case Study: Colibacillosis and Coccidiosis in Broiler Chicken Farm - Hartady, Tyagita Tyagita; Subagio, Reza Taufik; Khairani, Shafia (Faculty of Veterinary Medicine, Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2024)
Colibacillosis and coccidiosis are diseases that often infect broiler chicken. Escherichia coli is an opportunistic commensal bacterium. Colibacillosis often occurs as a secondary infection from other infectious diseases, such as coccidiosis. Coccidiosis is a digestive disease caused by Eimeria sp. Colibacillosis and coccidiosis cause stunting in chicken. This study was conducted to determine pathological features in colibacillosis and coccidiosis cases in broiler, as well as predisposing factors that can increase the risk of these diseases. The results of this study showed that colibacillosis causes pathological changes including peritonitis which is characterized by the formation of fibrinous exudate in the peritoneum, and inflammation of the air sacs. Coccidiosis causes hemorrhagic lesions in the small intestine and cecum. Water pipes that are corroded and overgrown with biofilms can become predispose factor to colibacilosis, because the biofilm layer facilitate the growth of E. coli and cause ineffective disinfection of drinking water. On the other hand, moist litter can promote Eimeria sp. oocysts sporulation; thereby increasing the risk of coccidiosis. In addition, moist litter also promote the growth of other disease agents such as bacteria and fungi.